2014
DOI: 10.1002/j.0022-0337.2014.78.8.tb05788.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Novel Module for Training Dental Students in Child Abuse Recognition and Reporting

Abstract: This study assessed the merits of introducing a novel, online interactive training module designed to positively engage dental students and teach them to recognize and report signs of child abuse and neglect. The study aimed to determine if the online training module educated the students equivalently or better than a lecture presentation of the same content. Seventy-two students from Columbia University College of Dental Medicine's class of 2015 (90 percent of the class) agreed to participate and were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 21 publications
3
28
0
1
Order By: Relevance
“…It was found that students' scores improved, both overall and in the areas of recognition and management of NAI, after the use of the e-learning module. Although no literature could be found on e-learning in this field specific to students, the results of this study are consistent with others based on clinicians and dental students, that showed elearning to be effective in improving management, detection and general knowledge of NAI (Smeekens et al, 2011;McEvoy et al, 2011;Shapiro, Anderson and Lal, 2014;Al-Dabaan, Asimakopoulou and Newton, 2015). They are also consistent with Dorsey et al's study (although based on child sexual abuse) showing that an e-learning package was effective in teaching medical students (Dorsey et al, 1996).…”
Section: Change In Score Between Pre-and Post-module Testssupporting
confidence: 91%
See 2 more Smart Citations
“…It was found that students' scores improved, both overall and in the areas of recognition and management of NAI, after the use of the e-learning module. Although no literature could be found on e-learning in this field specific to students, the results of this study are consistent with others based on clinicians and dental students, that showed elearning to be effective in improving management, detection and general knowledge of NAI (Smeekens et al, 2011;McEvoy et al, 2011;Shapiro, Anderson and Lal, 2014;Al-Dabaan, Asimakopoulou and Newton, 2015). They are also consistent with Dorsey et al's study (although based on child sexual abuse) showing that an e-learning package was effective in teaching medical students (Dorsey et al, 1996).…”
Section: Change In Score Between Pre-and Post-module Testssupporting
confidence: 91%
“…A variety of educational methods and tools have been studied in the field of NAI. Case-based learning, which involves applying knowledge and skills to clinical scenarios, has found to be effective in improving recognition and management in clinicians and dental students (Shapiro, Anderson and Lal, 2014;Anderst and Dowd, 2010;Tiyyagura et al, 2015). Possible reasons for this are that it creates context behind injuries and helps users look at preconceived ideas (Anderst and Dowd, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the 6 included RCTs were published between 2000 and 2014 in high-income countries: 5 were from the United States [43,46-49] and 1 was from the Netherlands [50]. All the studies included were parallel RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 La principal razón referida por los propios profesionales es la carencia de una formación académica universitaria que prepare al estudiante para el diagnóstico de esta situación. 4,8,9 Por tanto, es fundamental que los estudiantes de odontología reciban una adecuada formación sobre este tema para poder aumentar el número de casos denunciados por ellos en su futura práctica profesional. 6,8,10 El objetivo de esta investigación fue evaluar como la formación en atención odontológica pediátrica que actualmente se imparte en el Departamento de Odontología influye en los conocimientos y las actitudes de los estudiantes de grado respecto al MI y en su disposición a la denuncia de sospecha si se diera el caso.…”
unclassified